2019
DOI: 10.1101/584938
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Laser Recording of Subcellular Neuron Activities

Abstract: Advances in imaging and recording of neural activities with a single neuron resolution have played a significant role in understanding neurological diseases in the past decade. Conventional methods relying on patch-clamp and electrodes are regarded as invasive, whereas fluorescence-based imaging tools are useful but still suffer from a low signal-to-noise ratio and low sensitivity. Here we developed a novel optical imaging and recording system by employing laser emissions to record the action potentials in sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The process also proved to be reversible: neuron response can be fully recovered a few seconds after switching off the stimulus. 68 These works revealed the safe and reversible nature of the “US-activated piezoelectric nanoparticle stimulation” paradigm and highlighted a correlation between the US power intensity and the probability of activating the BTNP-incubated neurons.…”
Section: Engineering Biological Processesmentioning
confidence: 95%
“…The process also proved to be reversible: neuron response can be fully recovered a few seconds after switching off the stimulus. 68 These works revealed the safe and reversible nature of the “US-activated piezoelectric nanoparticle stimulation” paradigm and highlighted a correlation between the US power intensity and the probability of activating the BTNP-incubated neurons.…”
Section: Engineering Biological Processesmentioning
confidence: 95%
“…Integrated piezoelectric BaTiO 3 micromotors were capable of in situ electrical stimulation via the application of an external ultrasound field, further inducing differentiation in neural stem-like PC12 cells (Figure 1) [43]. In investigating the activation mechanism, Chen et al, through measuring the number of spines, calcium transients, and recovery time, confirmed that piezoelectric BaTiO3 nanoparticles can wirelessly activate neurons using ultrasound [41]. Building upon this research, they developed BTNPs decorated with a carbon shell and demonstrated its ultrasound-activated functionality in PC-12 neuron-like cells.…”
Section: Nerve Systemmentioning
confidence: 96%
“…In investigating the activation mechanism, Chen et al, through measuring the number of spines, calcium transients, and recovery time, confirmed that piezoelectric BaTiO 3 nanoparticles can wirelessly activate neurons using ultrasound [ 41 ]. Building upon this research, they developed BTNPs decorated with a carbon shell and demonstrated its ultrasound-activated functionality in PC-12 neuron-like cells.…”
Section: Application Of Piezoelectric Nanomaterials Activated By Ultr...mentioning
confidence: 99%